Implementation of The Power of Two Learning Model Operating Materials For Algebrial Form Based on The Power Point of Class VII High Schools - Dydik Kurniawan; Anita Sari; Tri Wahyuningsih (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
This research is a classroom action research project that aims to improve the mathematics learning outcomes of students in class VII Junior High School 6 Samarinda by using Microsoft PowerPoint to facilitate cooperative learning type The Power of Two on algebraic action material. The research was conducted at Junior High School 6 Samarinda, with 40 students in class VII1 as research subjects nd the object of research is cooperative learning type The Power of Two. Worksheets, final cycle tests, and observation sheets were used as instruments. LKS consists of LKS 1, 2, 3, 4, 5, and 6, which are done in groups in classrooms, as well as assessments at the end of each cycle. The descriptive statistics of averages and proportions were used in the data analysis technique. The analysis and discussion revealed that the type of cooperative going to lean. The research and discussion revealed that the form of cooperative learning used in The Power of Two with Microsoft PowerPoint is a small group learning consisting of two people who collaborate. Cycle I has a basic value of 54.7 and a final value of 66.1 with a 20.8 % increase in the proportion, cycle II has a basic value of 66.1 and a final value of 76.5 with a 15.7 % increase in the proportion, and cycle III has a base value of 76.5 and a final value of 83 with an 8.5 % increase in the proportion. The metrics for the teacher's behavior in the first cycle of accessing are good, the second cycle is good, and the third cycle is really good. As a result, cooperative learning is used to perfect it.